The effect of jujube extract consumption during two types of high intensity interval training and intensive endurance training on oxidative stress and antioxidant indices of liver tissue in immature male Wistar rats - Leila Youzbashi; Parisa Abdollahi; Ahmad Rahmani; Akram Karimiasl (فیزیولوژی ورزش و فعالیت بدنی, 2023)
Background and Purpose: One of the appropriate strategies for combating the adverse effects of oxidative stress caused by strenuous activities is consuming a well-balanced diet and taking antioxidant supplements. The purpose of this study was to investigate the effect of jujube extract consumption during two types of intermittent and intense endurance training on antioxidant indices and oxidative stress of the liver tissue of immature male rats.Materials and Methods: 72 male Wistar rats (aged= 22 days, weight= 60.64 ± 7.475 g) were randomly divided into nine groups after being weighed: control, placebo, jujube, intense endurance training (ICT), ICT + placebo, ICT + jujube gavage, high-intensity interval training (HIT), HIT + placebo gavage, HIT + jujube gavage. After a week of general and specific familiarization, the ICT protocol including running on the treadmill for four weeks (five sessions per week) with progressive duration and intensity and following the principle of exercise overload was implemented on an animal treadmill. So that the speed in the first week was equal to 10-18 meters per minute and its duration was 10-30 minutes, and in the last week the training speed reached 30 meters per minute and its duration was 55-60 minutes. The HIT training protocol was also carried out in the form of training with the pattern of seven-day courses (six days of training and one day of rest to prevent overtraining). Based on the principle of overload, training was applied in such a way that the training speed in the familiarization week was equal to 10-16 meters per minute and its duration was one minute, and in the last week the training speed reached 36-40 meters per minute (equivalent to about 85% of Vo2max). Distilled water was given to the placebo groups, and 600 mg/kg of jujube extract was given daily to the jujube groups after training. The activity of GPX, SOD, CAT enzymes, TAC and MDA was assayed by spectrophotometric method using diagnostic ELISA kit. ANOVA and Tukey's post hoc test were used to analyze the data.Results: The results showed that ICT and HIT significantly decreased MDA activity (P < 0.05). However, ICT and HIT did not affect the activity levels of antioxidant enzymes (SOD, GPX) and TAC (P > 0.05). On the other hand, HIT training significantly increased CAT enzyme (P < 0.05). The results also showed that groups with jujube gavage did not have a significant effect on the activity levels of antioxidant enzymes (SOD, GPX, CAT), TAC and MDA (P > 0.05).Conclusion: it seems that ICT, HIT moderates oxidative indices, and HIT training improves the antioxidant index CAT in immature rats.